Development of Indonesian Original Medicines Study of Standardized Herbal Medicine Products "Antangin JRG" as Traditional Medicine - Kornelia, Sindi; Hakim, Ali Rakhman; Sagita, Ririn; Azizah, Siti; Jubaidah, Siti (PROMOTOR, 2024)
This study aims to examine the potential for the development of indigenous Indonesian medicines based on traditional medicinal plants. Herbal medicine has been used for generations in Indonesia and has great potential to be developed into more standardized and modern products. This study covers various aspects ranging from product name, content, class, composition, efficacy claims, empirical data, standardization of raw materials, preclinical tests, toxicity tests, to clinical trials. The results of the study show that with proper processing and standardization, Indonesian traditional medicine can compete with modern pharmaceutical products.